Invitation to Self-Compassion: Reshaping Burden of Care in the Light of Self-Compassion Training Given to Relatives of Patients Hospitalised in Palliative Care - Karakurt, Nurgul; Erden, Yasemin; Turan, Gulcan Bahcecioglu; Bakir, Ercan (Wiley, 2025)
Aim: This study was conducted to investigate the effects of self-compassion training given to the relatives of patients hospitalised in the palliative care unit on the care burden and self-compassion of patient relatives. Method:The study is a randomised, controlled experimental study in pretest-posttest design. The study was conducted between February 2024 and June 2024 with the relatives of the patients who received care and treatment in the palliative care unit of a hospital in eastern Turkey. The study was completed with 30 patient relatives in the intervention group and 32 patient relatives in the control group. The patient relatives in the intervention group received 40-50 min of self-compassion training for 8 weeks. No intervention was given to the control group. Personal Information Form, Self-Compassion Scale, and Caregiver Burden Scale were used to collect the data. Results: While there was no significant difference in the total mean scores of the caregiver burden scale and self-compassion scale of the intervention group before the intervention compared to the control group (p > 0.05), a significant difference was found after the intervention (p < 0.05). When the regression coefficients were analysed, it was found that self-compassion training negatively affected the total mean score of the caregiver burden scale and explained 55% of its variance, while it positively affected the total mean score of the self-compassion scale and explained 55% of its variance. Conclusion:This study shows that self-compassion training given to the relatives of patients hospitalised in the palliative care unit is effective in terms of reducing the burden of care and increasing their self-compassion. Relatives of patients who received self-compassion training experienced a decrease in their care burden and an increase in their self-compassion. These findings emphasise the importance of self-compassion training in supporting the relatives of patients in palliative care.
Keywords: nursing; palliative care; patient relative; self-compassion